The inventory of activities in the framework of developing a European Union Arctic Policy - European Union, EU
Accompanying the document Joint communication: Developing a European Union Policy towards the Arctic Region: progress since 2008 and next steps (http://library.arcticportal.org/1698/) This staff working document accompanies the Joint Communication to the European Parliament and the Council on Developing a European Union Policy towards the Arctic Region: progress since 2008 and next steps. The purpose of the staff document is to give detailed information about the progress outlined since the Communication of 20 November 2008 on ‘The European Union and the Arctic Region’. It covers activities undertaken by the Commission services, the relevant European agencies and the European External Action Service (EEAS) on the proposals set out in the 2008 Communication as addressed under the guidance of the 2009 Council Conclusions and the 2011 European Parliament Resolution, in consultation with the EU Member States and in dialogue with the other Arctic states and other Arctic stakeholders.